2016
DOI: 10.17843/rpmesp.2016.334.2555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de las otoemisiones acústicas en relación a los potenciales evocados auditivos de tronco cerebral en niños

Abstract: To determine the validity of the use of acoustic otoacoustic emissions in comparison with the evoked potentials Auditory brainstem examination (PEATC), a study was carried out with 96 children between 0 and 4 years of age that went to Instituto Nacional de Rehabilitación in Lima, Peru. The results show a cut-off point corresponding to 1 in (+): 17.67 in right ear and 16.72 in left ear, and LR (-): 0.25 in ear right and 0.24 in left ear; ROC curve with area under the right ear curve of 0.830 (p<0.001) was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…[16][17][18] In a study conducted in Peru in children aged 0 to 4 years, it was concluded that the sensitivity and specificity of otoacoustic emissions were lower compared to BAEPs. 19 However, the choice between BAEPs and otoacoustic emissions is based on available resources and patient characteristics, so the normal values for each test in the population analyzed should be known.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In a study conducted in Peru in children aged 0 to 4 years, it was concluded that the sensitivity and specificity of otoacoustic emissions were lower compared to BAEPs. 19 However, the choice between BAEPs and otoacoustic emissions is based on available resources and patient characteristics, so the normal values for each test in the population analyzed should be known.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] En un estudio realizado en Perú con niños de 0 a 4 años, se concluyó que la sensibilidad y especificidad de las emisiones otoacústicas eran menores en comparación con los PEAT. 19 Sin embargo, la elección de PEAT o emisiones otoacústicas se basa en la disponibilidad de recursos y las características de los pacientes, por lo que se deben conocer los valores normales de cada estudio en la población.…”
Section: Discussionunclassified
“…El Joint Comité on Infant Hearing (JCIH), en su última edición señala una serie de factores de riesgo para hipoacusia, que incluye también factores para hipoacusia de aparición tardía en niños 7,12,13 . (véase tabla 1) Los factores de riesgo que incluye el JCIH son 11, entre maternos, perinatales y posnatales, siendo los factores más estudiados: Infecciones de la madre en el embarazo confirmadas o de sospecha por citomegalovirus, toxoplasma, herpes, rubéola, sífilis o virus de la inmunodeficiencia humana; meningitis bacteriana o viral; ingreso a unidad de cuidados intensivos mayor de 5 días que incluya oxigenación; síndromes asociados a hipoacusia 14 .…”
Section: Factores De Riesgounclassified